Exploring the Dynamics of Job Performance and Job Satisfaction on Work Effectiveness: A Study at BPMP Yogyakarta During COVID-19 - Jusniati Sari; Nora Saiva Jannana; Maksim Kim (MANAGERIA: Jurnal Manajemen Pendidikan Islam, 2023)
This study investigates the impact of job performance and job satisfaction on employee work effectiveness at the Yogyakarta Special Region Education Quality Assurance Institute amid the COVID-19 pandemic. Addressing the novel challenges posed by the work-from-home policy, the research aims to elucidate the direct influence of these variables in a transformed work environment. Utilizing a stratified random sampling method based on Slovin's formula, the study engaged 82 employees from BPMP Yogyakarta, employing bivariate correlation and double linear regression analysis. The results revealed a strong positive correlation between job performance and work effectiveness (Pearson Correlation: 0.883), with job performance and satisfaction collectively accounting for 82.7% of work effectiveness (R Square: 0.827). These findings highlight the critical role of job performance and satisfaction in enhancing work effectiveness, especially under pandemic-induced remote working conditions. However, the study's context-specific nature and reliance on self-reported measures suggest caution in generalization. The study's implications are significant for human resource strategies in similar institutions, advocating the need for adaptable and resilient work environments in challenging times. Future research should extend these findings to various organizational contexts and explore the long-term implications of remote working on these variables.